De novo generation of a bright blue fluorophore from 2-oxoglutarate in biological samples. Issue 2 (7th December 2021) - Kim, Yumin; Kang, Sangyoon; Lee, Byung Hun; Song, Youngjun; Kang, Sunah; Park, Hye Yoon; Lee, Yan
Abstract : DTPP, a bright fluorophore with 2-pyridone and γ-lactam, is generated in a de novo manner from non-fluorogenic 2-oxoglutarate and specific amines. The DTPP-based fluorometry is applied to the analysis of 2-oxoglutarate in a biological sample. Abstract : We discovered the generation of a new bright blue fluorophore from a particular type of amine and 2-oxoglutarate (2-OG) under mild conditions without any chemical additives. Two β-aminoethylamine molecules and three 2-OG molecules form an unprecedented 2-pyridone structure with a fused γ-lactam ring (DTPP) via complex reactions including double decarboxylation and quintuple dehydration. The DTPP fluorophore shows a high quantum yield (80%) and photostability. The great potential of the present DTPP generation in the quantitative analysis of 2-OG in biosamples is demonstrated.